CLIMATE CHANGE AND LIVELIHOOD PROBLEM OF FISHING COMMUNITIES WHO ARE LIVING IN LARGEST WETLAND OF ASSAM NAMED AS SONE BEEL - Das, Suranjan; Bhattacharjee, Jhimli (European Scientific Journal, ESJ, 2015)
Sone beel is the largest wetland in Assam. Ecological degradation of North-East India in general and of Sone beel of Barak Valley region of Assam in particular causes survival problem of the people who are directly dependent on it for their livelihood. A vast majority of people of Sone beel belonging to Kaibarta and Patni community who are in threat for earning livelihood due to gradual ecological change. This paper highlights how they are accepting the challenges for survival due to ecological change.